ArgR-Independent Induction and ArgR-Dependent Superinduction of the astCADBE Operon in Escherichia coli - Kiupakis, Alexandros K. (American Society for Microbiology, 2002)
For Escherichia coli, growth in the absence of ammonia is termed nitrogen limited and results in the induction of genes that assimilate other nitrogen sources, a response mediated by σ(54) and nitrogen regulator I (NR(I), also called NtrC). The astCADBE operon, which is required for growth with arginine as the sole nitrogen source, is moderately expressed during general nitrogen limitation and maximally expressed in the presence of arginine. The operon is also induced in stationary phase. Primer extension analysis of E. coli revealed the presence of a σ(54)-dependent promoter utilized in exponential phase during nitrogen limitation and a σ(S)-dependent promoter active during stationary phase. We used an ast-lacZ fusion to show that arginine stimulates expression, that ArgR, the arginine repressor, enhances expression from both promoters but is not essential, and that transcription by the two forms of the RNA polymerase is competitive and mutually exclusive. We demonstrated the binding of RNA polymerase holoenzymes, NR(I), and ArgR to the promoter region in vitro. We also reconstituted transcription from both promoters with purified components, which confirmed the accessory role of ArgR for the σ(54)-dependent promoter. Thus, the ast operon exhibits nitrogen source-specific induction that is unique for an NR(I)-dependent gene. The transcriptional regulation of the ast operon in E. coli differs from that in Salmonella enterica serovar Typhimurium, in which ArgR is required for ast operon expression.